Association between CARD14 gene polymorphisms and psoriasis vulgaris in Hainan Han population based on exon sequencing: A case-control study. Issue 40 (7th October 2022) - Msafiri Makene, Antonia; Liu, Jun-lin
Abstract : Psoriasis is a serious non-communicable, chronic immune-inflammatory mediated disease affecting about 125 million people worldwide. Its effects go beyond skin manifestation. Through genome-wide association studies, the caspase recruitment domain family member 14 (CARD14) gene and other gene variants have been implicated to have an association with Psoriasis, and as we move towards individualized therapy the discovery of single nucleotide polymorphism (SNP) is of great importance. This study aimed to determine whether the CARD14 gene is a susceptible gene for psoriasis vulgaris. In this study, 101 psoriasis patients and 79 healthy controls were subjected to exome sequencing. The CARD14 gene regions upstream and downstream of 1kb were sequenced. SNP-based association analysis and haplotype-based association analysis were performed in SNPs with minimum allele frequency (MAF) greater than 1%. Bioinformatic methods were used to predict the impact of risk loci on gene function. A total of 32 polymorphisms were identified in this study, of which 3 SNPs (1 in exon and 2 in intron) were susceptible to psoriasis ( P < .05, OR = 0.19 0.53, 95%CI = 0.05 0.70). Bioinformatics analysis showed that rs144475004 located on the exon led to an amino acid change from aspartate to histidine. On the other hand, results of haplotype-based association analysis showed that 2 haplotypes (CARD14-1 and CARD14-2) were protective haplotypes of the disease ( P < .05, OR = 0.18 0.38, 95%CI = 0.05 0.88), the frequencies in healthy controls and patients was 6.96% and 1.49%, respectively. CARD14 gene is associated with susceptibility to psoriasis vulgaris in the Hainan Han population.